Analisis Struktural Puisi “ Aku Ingin” Karya Sapardi Djoko Damono (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Poetry research can be defined as the result of research or the process of analyzing poetry. Poetry is one type of literary genre that expresses the poet's feelings. The series of words are beautiful, contain deep meaning and touch the hearts of the readers. This research aims to know and describe the physical structure and inner structure of poetry contained in the poem Aku Ingin by Sapardi Djoko Damono with a structural approach. The method used in this research is descriptive qualitative method, namely science that aims to describe the deep and intact content in the poem "Aku Ingin" by Sapardi Djoko Damono. The approach used is a structural approach, a structural approach tries to examine poetry into elements or structures that build and function. The data collection technique used is reading literature. The result of this research is the discovery of the entire physical structure and inner structure in the poem Aku Ingin. Physical structure in the form of poetry form, diction, language style, concrete words, imagery. While the inner structure in the form of theme, tone, atmosphere, and mandate.